KRIP6: a novel BTB/kelch protein regulating function of kainate receptors - Laezza, Fernanda (2007)
Whereas many interacting proteins have been identified for AMPA and NMDA glutamate receptors, fewer are known to directly bind and regulate function of kainate receptors. Using a yeast two-hybrid screen for interacting partners of the C-terminal domain of GluR6a, we identified a novel neuronal protein of the BTB/kelch family, KRIP6. KRIP6 binds to the GluR6a C-terminal domain at a site distinct from the PDZ-binding motif and it co-immunoprecipitates with recombinant and endogenous GluR6. Co-expression of KRIP6 alters GluR6 mediated currents in a heterologous expression system reducing peak current amplitude and steady-state desensitization, without affecting surface levels of GluR6. Endogenous KRIP6 is widely expressed in brain and overexpression of KRIP6 reduces endogenous kainate receptor-mediated responses evoked in hippocampal neurons. Taken together, these results suggest that KRIP6 can directly regulate native kainate receptors and provide the first evidence for a BTB/kelch protein in direct functional regulation of a mammalian glutamate receptor.